Vicki Belo ang batang nagpalaganap ng ganda The girl who spread beauty - Evasco, Eugene Y.; Ranola, Jonathan G.; Villalon, Mixkaela (Quezon City LG & M, 2013)
"This book narrates the story of Dr. Vicki Belo's life--how a shy child transformed and became a successful cosmetic surgeon in the Philippines. The story highlights Vicki's extraordinary diligence to improve herself, her knowledge, and abilities, to become successful with her business ventures."
Text in Filipino and English.